2020
DOI: 10.13057/biodiv/d210222
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of suitability and carrying capacity of mangrove ecosystem for ecotourism in Lembar Village, West Lombok District, Indonesia

Abstract: Abstract. Sukuryadi, Harahab N, Primyastanto M, Semedi B. 2020. Analysis of suitability and carrying capacity of mangrove ecosystem for ecotourism in Lembar Village, West Lombok District, Indonesia. Biodiversitas 21: 596-604. Mangrove ecosystems in Lembar Village, West Lombok District, Indonesia has high ecological role and economic potentials, and have been as a pilot area for mangrove conservation and rehabilitation activities. In 2015 the area was developed into a mangrove ecotourism area as a form of utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This study found that the carrying capacity of mangrove tourism in KJNP is 104 people/day. Compared to mangrove ecotourism in Lembar Village, West Lombok District, the carrying capacity of mangrove ecotourism is 33 people/day (Abdillah et al 2020). The difference in carrying capacity is due to the different lengths of tracking mangroves.…”
Section: Mangrove Ecotourism Carrying Capacitymentioning
confidence: 98%
“…This study found that the carrying capacity of mangrove tourism in KJNP is 104 people/day. Compared to mangrove ecotourism in Lembar Village, West Lombok District, the carrying capacity of mangrove ecotourism is 33 people/day (Abdillah et al 2020). The difference in carrying capacity is due to the different lengths of tracking mangroves.…”
Section: Mangrove Ecotourism Carrying Capacitymentioning
confidence: 98%
“…a typical preparation from Pasar Rawa village. This activity can be part of a series of tourist trips including Mangrove Plants which is one of the educational tours (Abdillah & Harahab, 2020).…”
Section: Internal Factor Analysismentioning
confidence: 99%
“…2.5. (Islam et al, 2011;Abdillah et al, 2020). Thus, here, high population densities (>200 persons/sq km) are assigned with low priority (Code 2), and low-population densities are allocated with high priority (Code 8).…”
Section: Social Parametersmentioning
confidence: 99%